Effects of Micropore Group Spacing and Irrigation Amount on Soil Respiration and Yield of Tomato with Microsprinkler Irrigation under Plastic Film in Greenhouse. (21st January 2021) - Zhang, Mingzhi; Yan, Xiaoqun; Lu, Zhenguang; Bai, Qingjun; Zhang, Yushun; Wang, Donglin; Zhou, Yuangang; Yin, Yuqing
Abstract : Microsprinkler irrigation under a plastic film in the greenhouse (MSPF) is a water-saving way which adopts the porous discharge form of a pipe under the plastic film. The effects of different micropore group spacings (L1:30 cm, L2: 50 cm) and irrigation amounts [I1: 0.7 Epan; I2: 1.0 Epan; and I3: 1.2 Epan (Epan is the diameter of 20 cm standard pan evaporation, mm)] of the MSPF on the soil respiration and yield of tomato were studied. A completely randomized trial design was used, and drip irrigation under plastic film (CK1) and microsprinkler irrigation (CK2) were also used as controls. The results showed that under the same irrigation amount, the soil respiration rate, tomato yield, and water use efficiency (WUE) of MSPF in spring and autumn are 8.09% and 6.74%, 19.39% and 4.54%, and 10.03% and 2.32% higher than those of CK1, respectively; they are significantly increased by 31.02% and 20.46%, 49.22% and 38.38%, and 58.05% and 34.66% compared with those of CK2, respectively, indicating that MSPF increased the amount of CO2 emission, but tomato yield and WUE were effectively improved, and a dynamic balance was reached among them. Compared with the 50 cm micropore group spacing, the spring and autumn tomato yields and WUE under the 30 cm micropore group spacing were significantly increased by 16.00% and 13.01% and 20.85% and 14.25%, respectively, and the micropore group spacing had no significant effect on the soil respiration rate in both root and nonroot zones. When the I increased from 0.7 Epan to 1.2 Epan, the soil respiration rate and yield in the root and nonroot zones of the spring and autumn tomatoes increased at first and then decreased, and the WUE showed a decreasing trend. The relationship of soil respiration rate between the nonroot and root zones obeys a logarithmic function, and the soil respiration rate in the nonroot zone has a quadratic curve relationship with the yield of tomato. This study can provide data support for the development of water-saving irrigation and yield increase of facility agricultural tomato and the analysis of the soil carbon cycling mechanism.